Cassane diterpenoids with α-glucosidase inhibitory activity from the fruits of Pterolobium macropterum - Cheenpracha, Sarot; Chokchaisiri, Ratchanaporn; Ganranoo, Lucksagoon; Bureekaew, Sareeya; Limtharakul, Thunwadee; Laphookhieo, Surat (Beilstein Journal of Organic Chemistry, 2023)
Two new cassane diterpenoids, 14β-hydroxycassa-11(12),13(15)-dien-12,16-olide (1) and 6′-acetoxypterolobirin B (3), together with a known analogue, identified as 12α,14β-dihydroxycassa-13(15)-en-12,16-olide (2), were isolated from the fruits of Pterolobium macropterum. Compound 1 is a cassane diterpenoid with a Δ11(12) double bond conjugated with an α,β-butenolide-type, whereas compound 3 is a dimeric caged cassane diterpenoid with unique 6/6/6/6/6/5/6/6/6 nonacyclic ring system. The structures of 1 and 3 were characterized by extensive spectroscopic analysis combined with computational ECD analyses. The α-glucosidase inhibitory activity of isolated compounds was evaluated, and compounds 1 and 3 showed significant α-glucosidase inhibitory activity with IC50 values of 66 and 44 μM.
Keywords: α-glucosidase inhibitory activity; cassane diterpenoid; Fabaceae; medicinal plant; Pterolobium macropterum